Relocation to Get Venture Capital: A Resource Dependence Perspective. (July 2019) - De Prijcker, Sofie; Manigart, Sophie; Collewaert, Veroniek; Vanacker, Tom
Using a resource dependence perspective, we theorize and show that non-venture-capital-backed ventures founded in U.S. states with a lower availability of venture capital (VC) are more likely to relocate to California (CA) or Massachusetts (MA)—the two VC-richest states—compared to ventures founded in states with a greater availability of VC. Moreover, controlling for self-selection, ventures that relocate to CA or MA subsequently have a greater probability of attracting initial VC compared to ventures that stay in their home state. We discuss the implications for theory, future research, and practice.